2003
DOI: 10.1203/01.pdr.0000069841.52414.a5
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Produced by the Enterocyte Is Involved in the Cellular Regulation of Ion Transport

Abstract: The role of nitric oxide (NO) in the intestinal basal ion transport and under conditions of enterotoxin-induced ion secretion is controversial. Namely it is not clear whether NO enhances or counteracts intestinal ion secretion and whether the effects on transport result from a direct interaction with the enterocyte. The cell origin of NO is also unclear. We have tested the hypothesis that NO produced by the enterocyte directly regulates ion transport processes either in basal condition or in response to choler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…First, the elimination of ADM-stimulated increases in [Ca 2ϩ ] i with H-89 or Rp-cAMP suggests that PKA mediates ADM-stimulated NO production by stimulating accumulation of intracellular Ca 2ϩ . Likewise, this PKA-Ca 2ϩ -NO cascade has been reported in urothelial cells (Birder et al, 2002), enterocytes (Canani et al, 2003), and neuroblastoma cells (Xu and Krukoff, 2005). Alternatively but not exclusively, PKA may stimulate nNOS activation by activating protein phosphatases to remove the inhibitory serine 847 phosphorylation from nNOS.…”
Section: Discussionmentioning
confidence: 70%
“…First, the elimination of ADM-stimulated increases in [Ca 2ϩ ] i with H-89 or Rp-cAMP suggests that PKA mediates ADM-stimulated NO production by stimulating accumulation of intracellular Ca 2ϩ . Likewise, this PKA-Ca 2ϩ -NO cascade has been reported in urothelial cells (Birder et al, 2002), enterocytes (Canani et al, 2003), and neuroblastoma cells (Xu and Krukoff, 2005). Alternatively but not exclusively, PKA may stimulate nNOS activation by activating protein phosphatases to remove the inhibitory serine 847 phosphorylation from nNOS.…”
Section: Discussionmentioning
confidence: 70%
“…An active role of the enterocyte in ion transport has been hypothesized (35). We have reported that the enterocyte responds to an enterotoxin-induced secretion through the activation of constitutive nitric oxide synthase functioning as a breaking force of ion secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in nitrotyrosine staining between controls and infected embryos were most notable at 5 dpi. This observation was significant, since fluid accumulation in infected embryos was not detected until 5 dpi, suggesting NO may be involved in fluid accumulation by affecting enterocyte barrier function and ion transport (6,28,31). The source of the NO in vivo is unknown.…”
Section: Cd4mentioning
confidence: 98%